The Meaning of the Word Raja'a in the Al-Quran (Toshihiko Izutsu's Semantic Approach) - Siti Mukmin; Bahrudin Zamawi (Tilawah: Journal of Al-Qur'an Studies, 2025)
This study explores the development of the meaning of the word Raja’a in the Qur’an using Toshihiko Izutsu’s semantic approach. The research aims to enrich Qur’anic semantic studies and provide a deeper understanding of the concept of Raja’a. Lexically, Raja’a is defined in Arabic dictionaries as “to return” or “once again,” while in the Qur’an it carries various meanings such as rain, return, repentance, restoration, and death. This research is a qualitative library study, with primary data consisting of Qur’anic verses containing the word Raja’a, Toshihiko Izutsu’s God and Man in the Qur’an, and several Arabic lexicons. The findings show that Raja’a appears 104 times in 98 verses across 43 surahs. Based on Izutsu’s semantic analysis, the basic meaning of Raja’a is “to return,” while its relational meanings include “to repent,” “to reconcile,” “rain,” and “Allah as the ultimate return.” Diachronically, in the pre-Qur’anic period Raja’a simply meant “to return” without religious connotation, but in the Qur’anic period its meaning expanded into a spiritual concept reflecting the relationship between humans and God. The weltanschauung of Raja’a signifies “returning to the origin,” referring to the return of all things to their initial state or source.